Faktor Presdisposing dan Reinforcing Yang Mempengaruhi Penggunaan Metode Kontrasepsi Suntik 3 Bulan Diwilayah Kerja Puskesmas Garung Kabupaten Wonosobo - Haryono, Nathasia Elga; Sinaga, Sri Putriani; Ladyvia, Fiyola; Khaerunisa, Ismah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The 3-month injectable contraceptive is the most widely used method in the working area of Puskesmas Garung, accounting for 50% of the total active contraceptive coverage, which stands at 78.90%. However, this method has several drawbacks, such as an effectiveness rate of only 98% and a failure risk of 60 per 1,000 users according to WHO, which is higher compared to IUDs, implants, MOW, and MOP. The high usage of the 3-month injectable contraceptive may lead to suboptimal birth control, potentially increasing maternal mortality rates (MMR). This study aims to identify predisposing and reinforcing factors influencing the selection of the 3-month injectable contraceptive. Using a descriptive qualitative method with consecutive sampling involving 9 respondents, data were collected through questionnaires and analyzed univariately. The findings indicate that age, education, and knowledge (predisposing factors) are the most influential factors in choosing this contraceptive method. Therefore, healthcare providers are encouraged to offer in-depth counseling on the effectiveness and drawbacks of the 3-month injectable contraceptive to encourage mothers to switch to long-acting contraceptive methods (LACMs).